O RETORNO DO EXILADO EM O ANO DA MORTE DE RICARDO REIS, DE JOSÉ SARAMAGO - Santos, Tiago Ribeiro dos (Revista Desassossego, 2010)
This article includes a study of Saramago's text in alignment with the concept of flaneur coined by Walter Benjamin. We intend to outline how the diasporic character can be seen as a drifter who wanders the streets of Lisbon in the midst of “the bad weather” of a troubled year.